PENGARUH PERKEMBANGAN ZAMAN TERHADAP KEDUDUKAN PEREMPUAN DALAM HUKUM WARIS ADAT BALI - Rudi, I Ketut (Belom Bahadat, 2022)
Balinese society is a society that is thick an obedient to tradition, culture and customary law. The development of globalization an scince and technology does not necessarily shake or change the customs an traditions of the Balinese people. Balinese cutomary law prioritizes the position of men in term of inhertance an family matter. When viewed from the side of the role in the family, in todays era women an men are almost in contrast. For axample in education, politics, goverment an so on, women have the same opportunitties an even take the same roles. Likewise in the family, women can replace the position of men as head of the family an breadwinner if the condition of men as husbands is no longer possible. Different conditions will be found in terms of Balinese cutomary inheritance law. In general, women are not given the same opportunities as men, and it can even be said that they do not have the right to participate in the inheritance or as heirs. So when viewed from the perspective of gender equality, it will create a discriminatory impression against women. However, in principle, Balinese women accept such a situation and do not consider this a disadvatage. Because this has become a habit that has been passed down from generation to generation. Keyword: Inheritance Law, Balinese Custom, Gender